Histological Examination of Tissue Obtained in Early Pregnancy Loss - Kayastha, S.; Shah, L.; Mainali, S. (Kathmandu University Medical Journal, 2021)
Background It is a routine practice to send histological sample after surgical evacuation of early pregnancy loss. Objective This study was carried out to see the justification of regular histological study by carrying out the histological study of early pregnancy loss and to find the prevalence of gestational trophoblastic disease in early pregnancy loss. Method It was a descriptive prospective study, conducted in Nepal medical college teaching hospital from February to October 2020 in Obstetrics and Gynaecology department. Clinical data such as age, parity, gestational age and diagnosis were collected of 130 patient of early pregnancy loss. Then histological study were sent after surgical evacuation. Result Among the age group, 21-30 age group was maximum. (64.61%), more than half of the patient was primigravida (53.07%) and most of the cases were between 6 to 9 weeks of gestation. Incomplete abortions were maximum (43.07%), missed abortions 38.46%, blighted abortions 16.15%, enevitable abortions 1.53% and septic abortion was 0.76%. Among histological finding, 72.30% were product of conception, 15.38% of the cases had no product of conception, decidual tissue only in 6.92%, partial mole in one case (0.76%), complete mole in one case (0.76%) and hydrophic changes in one case (0.76%). The total cases of Gestational trophoblastic diseases (GTD) were 3(2.30%). Conclusion In our study we found 2.3% of cases of GTD, which was quite high in compare to Western word. So it is a good practice to do histological study of all cases of EPL in our country to detect GTD, determining cause for recurrent pregnancy loss and detecting unexpected fetal pathology.